Role of Cholesterol and Lipid Rafts in Cancer Signaling: A Promising Therapeutic Opportunity? - Vona, Rosa; Iessi, Elisabetta; Matarrese, Paola (Frontiers in Cell and Developmental Biology, 2021)
Cholesterol is a lipid molecule that plays an essential role in a number of biological processes, both physiological and pathological. It is an essential structural constituent of cell membranes, and it is fundamental for biosynthesis, integrity and functions of biological membranes, including membrane trafficking and signaling. Moreover, cholesterol is the major lipid component of lipid rafts, a sort of lipid-based structures that regulate the assembly and functioning of numerous cell signaling, including those related to cancer, such as tumor cell growth, adhesion, migration, invasion and apoptosis. Considering the importance of cholesterol metabolism, its homeostasis is strictly regulated at every stage: import, synthesis, export, metabolism and storage. The alterations of this homeostatic balance are known to be associated with cardiovascular diseases, and atherosclerosis, but mounting evidence also connects these behaviors to increased cancer risks. Although there is conflicting evidence on the role of cholesterol in cancer development, most of studies consistently suggest that a dysregulation of cholesterol homeostasis could lead to the cancer development. This review aims to discuss the current understanding of cholesterol homeostasis in normal and cancerous cells, summarizing key findings from recent preclinical and clinical studies that have investigated the role of major players in cholesterol regulation and the organization of lipid rafts, which could represent promising therapeutic targets.